1989
DOI: 10.1099/0022-1317-70-9-2421
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phosphorylation of the Nucleoprotein of Influenza A Viruses

Abstract: SUMMARYAn analysis of the nucleoprotein (NP) of 29 different influenza A viruses by phosphopeptide fingerprinting revealed three prototype patterns. The first, which was a complex pattern consisting of six to seven phosphopeptides, another which was relatively simple consisted of two or three phosphopeptides, and a third one which was complex but was missing the main phosphopeptide shared by the two other patterns. Phosphoserine was the only labelled phosphamino acid detected. A tentative deduction of two of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 17 publications
3
79
0
Order By: Relevance
“…These studies reported that the drugs DRB and LB, which were added at the beginning of the infection, did not inhibit viral mRNA synthesis completely and that viral transcripts were retained in the nucleus, consistent with our microscopy results. In addition, the Protein Kinase C Inhibior [also known as 1-(5-isoquinolinesulphonyl)-2-methylpiperazine dihydrochloride, kinase inhibitor H7] was found to block viral late gene expression but not the viral RNA [18,19]. Vogel et al [30] showed that the H7 resulted in retention of HA in the nuclei of infected chick embryo fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that the drugs DRB and LB, which were added at the beginning of the infection, did not inhibit viral mRNA synthesis completely and that viral transcripts were retained in the nucleus, consistent with our microscopy results. In addition, the Protein Kinase C Inhibior [also known as 1-(5-isoquinolinesulphonyl)-2-methylpiperazine dihydrochloride, kinase inhibitor H7] was found to block viral late gene expression but not the viral RNA [18,19]. Vogel et al [30] showed that the H7 resulted in retention of HA in the nuclei of infected chick embryo fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitations were carried out as described 6 with a polyclonal rabbit antiserum against the N terminus of HA, when indicated (NHA), or with a polyclonal rabbit antiserum (P) against X-31 virus, which recognizes all forms of HA as well as the nucleoprotein (NP), which is a phosphoprotein [32][33][34] and can appear as either one or two bands in the gel depending on the phosphorylation status of the protein (A. Ora, Utrecht University, and I.B., unpublished observations). To probe for different conformations, two mouse monoclonal IgG antibodies, F1 and F2, made against nondenatured HA2 were used 6 .…”
Section: Immunoprecipitation and Sds-pagementioning
confidence: 99%
“…Restriction is said to be partial because of the evidence for occurrences of interspecies virus transmission, e.g., the finding of avian HlNl viruses in swine in Europe, human H3N2 viruses in swine, swine HlNi viruses in humans, and other avian viruses in seals, whales, and mink. (88,89,148). Also, avian NP specifically causes restricted replication of otherwise human viruses in squirrel monkeys (162).…”
Section: Molecular Determinants Of Host Range Restrictionmentioning
confidence: 99%